First lung transplant in Wuhan for a critical and elderly COVID‐19 patient. Issue 4 (1st September 2021) - Wang, Bo; Huang, Jie; Hsin, Micheal; Chen, Jingyu; Lin, Huiqing
Abstract: Introduction: We report the case of a 65‐year‐old Coronavirus disease 2019 (COVID‐19) patient with pneumonia and subsequent end‐stage pulmonary failure who required 63 days of mechanical ventilation (MV) and 62 days of extracorporeal membrane oxygenation (ECMO). Methods: On Day 45, a comprehensive interdisciplinary discussion on the best course of treatment resulted in the general consensus that his lungs would not recover. As such, he was evaluated and listed for a lung transplant. Results: We performed a bilateral lung transplant, and the patient was weaned off ECMO and MV postoperatively. This is the first report of lung transplants in patients with COVID‐19 in Wuhan. Conclusions: We suggest that a lung transplantation may be a viable treatment for patients with end‐stage pulmonary failure secondary to COVID‐19 in selected situations. Abstract : Lung transplantation provided an opportunity for this very severe selected patient a chance to survival, which is meaningful